Old-fashioned Education: Causes of the Collapse of Islamic Boarding Schools - Alfa Syifa' Qothrun Nada; Sutrisno (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2026)
This research is an expression, criticism, and recommendation from researchers to the leadership of the Al-Istiqomah Islamic boarding School to pay more attention to educational reform to revitalize the Islamic boarding school. The main problem is that old-fashioned education influences the existence of Islamic boarding schools in the era of globalization. This type of research is field research with a qualitative approach and uses descriptive analysis methods. Data collection in this research used interviews, observation, and documentation techniques. The data analysis technique is through reduction, presentation, and conclusion. The results of this research are: 1) the collapse of the Al-Istiqomah Islamic boarding school was motivated by the focus of the Islamic boarding school leadership only on education to memorize the Qur'an without being balanced with teaching how to understand the Qur'an well and correctly and how to apply it to everyday life. 2) Al-Istiqomah Islamic boarding school still uses the essence of policies passed down from generation to generation and seems traditional (old-fashioned) without paying attention to innovations as needed in the era of globalization. 3) The policies implemented by Islamic boarding school leaders have yet to be able to produce student output that is highly competitive in society. 4) the policy implications of Islamic boarding school leaders were found to produce alums who memorize the Koran with a mentality that is not yet ready to enter the world of work.